PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL, DAN LOAN TO DEPOISIT RATIO TERHADAP PERUBAHAN LABA ( Studi Kasus Bank Konvensional Yang Terdaftar di BEI Periode 2009-2012) - Dita Nur Raifah; Teguh Erawati (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
This study discusses the changes in earnings and financial ratios based on financial statements of listed companies in Indonesia Stock Exchange during the period 2009-2012. The purpose of this study was to determine whether the Capital Adequacy Ratio (CAR) , Non- Performing Loans (NPL) , Operating Expenses Operating Income (BOPO) , and the Loan to Deposit Ratio (LDR) has an influence on incomen changes. The type of data in this study is secondary . Sampling in this study using purposive sampling method . Companies that used a sample of 24 banking companies listed in Indonesia Stock Exchange during 2009-2012. This research is quantitative , and statistical tests use the test multiple linear regression. By using regression analysis , it can be seen that the Capital Adequacy Ratio (CA ) , Non Performing Loans (NPL) , Operating Expenses Operating Income (BOPO) , and the Loan to Deposit Ratio (LDR) has a significant effect on earnings changes . Partial test results , the Capital Adequacy Ratio (CAR) has a positive and significant effect on earnings changes . Non Performing Loan (NPL) had no effect on earnings changes . Operating Expenses Operating Income does not affect the income changes . Loan to Deposit Ratio (LDR) has a positive and significant effect on earnings changes. Keywords : Capital Adequacy Ratio (CAR) , Non-Performing Loans (NPL) , Operating Expenses Operating Income (BOPO) , and the loan to deposit ratio (LDR) , and Income Changes .